Bioenergy from Cotton Industry Wastes: A review and potential. (December 2016) - Hamawand, Ihsan; Sandell, Gary; Pittaway, Pam; Chakrabarty, Sayan; Yusaf, Talal; Chen, Guangnan; Seneweera, Saman; Al-Lwayzy, Saddam; Bennett, John; Hopf, Joshua
Abstract: Current estimates for world cotton production are about 25 million tonnes and accounting for 50 million tons of biomass waste. The options for utilising cotton biomass wastes include composting, gasification, pyrolysis, fermentation (ethanol), anaerobic digestion and direct incineration. Solid cotton gin waste cannot be directly reused on-farm due to farm hygiene risks. Composting either on-farm or at the gin is an accepted method for pathogen disinfection and pesticide degradation, although this option may face the problem of small market demand and possible disease concerns. On the other hand, on-farm cotton residues are fundamental for minimising losses in soil carbon, organic carbon content and surface protection. Converting these wastes to energy using various treatments such as gasification, pyrolysis and anaerobic digestion minimises the land required for processing, and the energy produced may offset the much higher capital costs involved. The scope of this study is to examine the size of cotton industry in Australia and the associated by-products produced. The strengths, weaknesses, opportunities and threats of different options for utilising cotton wastes throughout processing were examined. The technical, environmental and economic aspects of each waste management option have formed the basis of our conclusions and recommendations. It seems that pyrolysis of cotton stalks is a good option due to the potential revenue of 104 million dollars. Using cotton gin trash (CGT) for ethanol production is another option, and the average production would be around 33–47 million litres of ethanol for the entire industry. The revenue from this process can be 33–47 million (1/L). Cotton stalk provides the highest burning efficiency and longest burn time compared to corn stover and soybean residues. The potential amount of energy produced from burning cotton stalks can be around 24.8 PJ which is equivalent to 97 million worth of coal.